Endothelial replicative senescence delayed by the inhibition of MTORC1 signaling involves MicroRNA-107 - Khor, Eng Soon; Wong, Pooi Fong (Elsevier, 2018)
Accumulation of senescent endothelial cells can contribute to endothelium dysfunction. Suppression of MTOR signaling has been shown to delay senescence but the mechanism that underpins this effect, particularly one that involves miRNAs, remains to be further defined. This study sought to identify miRNAs involved in MTORC1-mediated inhibition of replicative senescence in endothelial cells. Pre-senescent HUVECs were prolonged treated with low dose rapamycin (1 nM), an MTOR inhibitor. Rapamycin treatment down-regulated the phosphorylated MTOR, RPS6 and 4EBP1 expressions, which confirmed MTORC1 suppression. Prolonged low dose rapamycin treatment has significantly reduced the percentage of senescence-associated beta galactosidase (SA-β gal) positively stained senescent cells and P16INK4A expression in these cells. On the contrary, the percentage of BrdU-labelled proliferating cells has significantly increased. RPTOR, a positive regulator of MTORC1 was knockdown using RPTOR siRNA to inhibit MTORC1 activation. RPTOR knockdown was evidenced by significant suppressions of RPTOR mRNA and protein expression levels. In these cells, the expression of miR-107 was down-regulated whereas miR-145-5p and miR-217 were up-regulated. Target gene prediction revealed PTEN as the target of miR-107 and this was confirmed by biotin pull-down assay. Over-expression of miR-107 has decreased PTEN expression, increased MTORC1 activity, induced cell cycle arrest at G0/G1 phase and up-regulated P16INK4A expression but mitigated tube formation. Collectively, our findings revealed that delayed endothelial replicative senescence caused by the inhibition of MTORC1 activation could be modulated by miR-107 via its influence on PTEN.